Robin Hood Supplementary Reading Material - Roderick Hunt; Roderick Hunt (Oxford Reading Tree, 2012)
The Level 6 Biff, Chip and Kipper Stories, written by Roderick Hunt and illustrated by Alex Brychta, provide a rich story context to help develop language comprehension and decoding skills. Stories, More Stories A and More Stories B involve familiar situations and a variety of fantasy settings through the magic key adventures. Books contain inside cover notes to support children in their reading. Help with childrens reading development is also available at www.oxfordowl.co.uk.